Bone‐forming cells with pronounced spread into the third dimension in polymer scaffolds fabricated by two‐photon polymerization. Issue 3 (5th December 2016) - Heitz, J.; Plamadeala, C.; Wiesbauer, M.; Freudenthaler, P.; Wollhofen, R.; Jacak, J.; Klar, T. A.; Magnus, B.; Köstner, D.; Weth, A.; Baumgartner, W.; Marksteiner, R.
Abstract: The main aim of this work was to stimulate bone‐forming cells to produce three‐dimensional networks of mineralized proteins such as those occurring in bones. This was achieved by a novel approach using a specific type of mesenchymal progenitor cells (i.e., primary fibroblast cells from human hair roots) seeded on to polymer scaffolds. We wrote polymer microstructures with one or more levels of quadratic pores on to a flexible substrate by means of two‐photon polymerization using a Ti‐sapphire femtosecond laser focused into a liquid acrylate‐based resin containing a photoinitiator. Progenitor cells, differentiated into an osteogenic lineage by the use of medium supplemented with biochemical stimuli, can be seeded on to the hydrophilic three‐dimensional scaffolds. Due to confinement to the microstructures and/or mechanical interaction with the scaffold, the cells are stimulated to produce high amounts of calcium‐binding proteins, such as collagen type I, and show an increased activation of the actin cytoskeleton. The best results were obtained for quadratic pore sizes of 35 µm: the pore volumes become almost filled with both cells in close contact with the walls of the structure and with extracellular matrix material produced by the cells. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 891–899, 2017.